EXPLORING THE MACROCOSMIC PERSPECTIVE OF THE BAYAN INDIGENOUS COMMUNITY IN BAYAN DISTRICT, NORTH LOMBOK - Surur, Fadhil; Shiraishi, Hideo (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
The Bayan customary community in North Lombok utilizes traditional knowledge systems, including awig-awig, to govern natural resources and sustain environmental harmony, grounded in concepts like Wetu Telu and shaped by Balinese culture. Despite the obstacles of industrialization, Indigenous and Local Knowledge (ILK) is essential for sustainable spatial planning, necessitating extensive research to bolster governmental initiatives. This study was executed in the Bayan sub-district of North Lombok, commencing with interviews of Pemangku Adat and Pembekel, subsequently followed by focus group discussions and participatory mapping. The investigation was performed using both spatial and non-spatial methods to elucidate the relationship between local knowledge and geographical characteristics. The Bayan customary people possess a concept of Indigenous Local Knowledge (ILK) that has been transmitted through generations to carefully manage their environment by delineating daya (mountain) and lauq (coastal) areas, overseen by perumbak, symbolizing harmony between the mountain and the sea. The connection between perumbak, daya, and lauq symbolizes the balance between a man and a woman, who collectively safeguard the source of life and defend their customary region from adverse external forces in the macrocosm.